2021
DOI: 10.15240/tul/001/2021-4-004
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Efficient Approach for Identification and Selection of Stakeholder Engagement Strategies: A Case Study

Abstract: The goals and objectives of a project as well as the needs, requirements and expectations of the project stakeholders may contradict or non-fulfillment of them may have different detrimental and negative consequences for the project. Therefore, project stakeholders should be effectively managed, but it is not possible to satisfy all project stakeholders and meet all of their expectations and requirements. As a result, project team must strike a balance between the project goals and objectives and the needs, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…These hypotheses provide the groundwork for further study and may direct the design of interventions to overcome the challenges indicated. It is crucial to learn what causes these roadblocks and what can be done about them [80,83]. These challenges must be overcome for BIM to be successfully implemented in Malaysia, which would improve the safety and risk management of oil and gas construction projects.…”
Section: B6mentioning
confidence: 99%
“…These hypotheses provide the groundwork for further study and may direct the design of interventions to overcome the challenges indicated. It is crucial to learn what causes these roadblocks and what can be done about them [80,83]. These challenges must be overcome for BIM to be successfully implemented in Malaysia, which would improve the safety and risk management of oil and gas construction projects.…”
Section: B6mentioning
confidence: 99%
“…It enhances the ability to promptly address stakeholder requirements, promotes cooperation, and permits modifications at various stages of the project's duration. However, the adoption of flexible planning and execution necessitates a culture transformation, which might pose difficulties when attempting to execute it inside conventional construction settings(Businessmap, 2024).Overall, the selection of a framework is contingent upon the unique setting of the project, the characteristics of the stakeholders involved, and the desired objectives(Khalilzadeh et al 2021).Project managers should carefully evaluate the advantages and disadvantages of each framework and implement a customised approach that aligns with their specific requirements. Project managers can enhance the probability of project success and establish enduring positive relationships with stakeholders by consistently involving them, resolving their concerns, and adjusting to their evolving requirements(Khalilzadeh et al 2021).…”
mentioning
confidence: 99%